Escitalopram-Associated Acute Urinary Retention in Elderly Men With Known or Latent Benign Prostatic Hyperplasia: A Case Series. Issue 6 (November 2016) - Ferentinos, Panagiotis; Margaritis, Dimitrios; Douzenis, Athanasios
Abstract : Abstract: Lower urinary tract outflow dysfunction is frequent in older men and a potential cause of serious complications such as acute urinary retention (AUR). Drug-induced AUR has only rarely been reported with selective serotonin reuptake inhibitors including escitalopram; reported cases had no history of urinary outflow dysfunction. We herein report the development of AUR after the introduction of escitalopram at a standard dose in 3 male patients with previously diagnosed or unknown/latent and nonsymptomatic benign prostatic hyperplasia. Urinary retention receded after escitalopram discontinuation in 2 cases but led to emergent prostatectomy in the third. This case series highlights escitalopram's potential association with AUR in elderly men with known or latent benign prostatic hyperplasia. Further studies are warranted to investigate whether compromised or marginal urinary outflow should be considered a contraindication for treatment with escitalopram.